My Indian boyhood - Standing Bear, Luther, 1868?-1939. (Lincoln, Neb. : University of Nebraska Press, 1988)
Standing Bear describes the home life and education of Indian children.
The Sioux -- Bows and arrows -- The Indian boy and his pony -- Hunting and fishing -- Plants, trees, and herbs -- Tanning, painting, and designing -- Games -- How chiefs are made -- Medicine men and music -- At last I kill a buffalo.
"Bison book."
Reprint. Originally published: Boston : Houghton Mifflin, 1931.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Standing Bear, Luther, -- 1868?-1939 -- Childhood and youth; Standing Bear, Luther, -- 1868?-1939.; Standing Bear, Luther, -- 1868?-1939; Lakota Indians -- Kings and rulers -- Biography; Indians of North America -- Great Plains -- Biography; Lakota Indians -- Social life and customs; Indians of North America -- Great Plains -- Social life and customs; Teton Indians -- Biography; Native Americans -- Great Plains -- Biography; Peuples autochtones -- Grandes Plaines -- Biographies; Lakota -- Mœurs et coutumes; Peuples autochtones -- Grandes Plaines -- Mœurs et coutumes; HISTORY -- State & Local; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; American Indians -- Teton; Biographies; American Indians -- Literature; American Indians -- Culture; Childhood and youth of a person; Indians of North America; Indians of North America -- Social life and customs; Lakota Indians -- Kings and rulers; Lakota Indians -- Social life and customs; Great Plains; Sioux; Indianer; Kultur; USA; collective biographies; autobiographies (literary works); Biographies; Biographies; Autobiographies; Biographies; Autobiographies